Literacy and Information - Achmad Tohari; Christopher Parsons; Anu Rammohan (Institute of Labor Economics (IZA), 2021)
Information campaigns aimed at empowering the poor often fall short of meeting their desired aims. We study literacy's role in determining their efficacy. First, exploiting an RD design, we show that receipt of information increased household rice receipts by 30 percentage points. Second, we show that approximately half of the effect is driven by household head literacy. Leveraging novel data on the locations and timings of school openings in the 1970s INPRES school building program, we document that household heads' literacy gained during childhood was pivotal for their households subsequently receiving their full entitlement of rice during adulthood.
Keywords: D04; D73; I21; I28; I32; I38; J24; O12; 330; poverty; targeting; information; literacy; dynamic complementarity